Trans-influence of nitrogen-and sulfur-containing ligands in trans-platinum complexes: A density functional theory study - Manalastas, William W. (Animo Repository, 2009)
Transplatin complexes with N-or S-containing ligands were modeled in silico. We performed density functional theory calculations using the B3LYP exchange-correlation functional as incorporated in the Gaussian03 software package. The 6-311+G(d,p) basis set was used for first-row elements, and the LanL2DZ with effective core potential (ECP) basis set was used for platinum. The various neutral N-or S-containing ligands do not give rise to considerable variations in the trans-bond lengths and strengths. The reactions leading to complex formation also yield close net energy values. Nevertheless, Pt complexes with anionic thiolate (CH3S-) ligand are significantly more energetically stable by at least ∼5eV (∼115kcalmol-1 or ∼484kJmol-1) compared to transplatin complexes with other ligands. An examination of the net energetic stabilities and dipole moments of transplatin complexes with N-and S-ligands led us to hypothesize adenine to be the most suitable candidate among naturally occurring organic ligands (X) for the development of trans-Pt(NR)(NR′)Cl(X) anticancer agent. © 2009 IOP Publishing Ltd.